El danzón en los estudiantes de Licenciatura en Comunicación Social de la Universidad de Matanzas. Su conocimiento y representación social - Mercadet Portillo, Nancy Narcisa; Ortega Suárez, Jorge Domingo (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
A priority objective of the Multicultural Studies “Fernando Ortiz” Department (CEMFO) is to raise the epistemic level of students of Social and Humanistic Sciences, respect to the intangible cultural heritage of the Cuban nation and its development in the province of Matanzas. The article informs the results of a research guided by qualitative and critic paradigms, focused on the knowledge and social representation of a sample of foreign languages students about danzón, created by musician Miguel Ramón Demetrio Faílde y Pérez (1852-1921) who premiered it in Matanzas, his hometown, on January 1, 1879; that as a rhythm it assimilated musical elements of cosmopolitan origin and, in turn, became basic with respect to others such as the danzonete (1929), the mambo (1938), popularized worldwide ten years later by another musician of Matanzas, Dámaso Pérez Prado (1916-1989); and the cha-cha-chá (1951). Based on the results of the research, the key epistemic concepts of a system of teaching activities were designed to develop, in the student worldview, knowledge and a positive social representation of the heritage value of the danzón. The authors are currently researching Social Communication students, with similar purposes to help their best future professional performance.